Macroalgae diversity at Porok Beach, Gunungkidul, Yogyakarta, Indonesia - Faradilla Faradilla; Fajriatin Nikmah; Alfi Dilla Putri; Gizela Aulia Agustin; Lailatul Nurkaromah; Melinda Windiana Febrianti; Muhammad Arief Budhiman; Umi Salamah; Abdul Razaq Chasani (Future Science, 2022)
Indonesia is one of the world's richest nations in terms of its biodiversity. One of the biological resources that has an important role in marine life is macroalgae. As a primary producer, macroalgae play an important role in the coastal environment. Porok Beach is a beach in the Gunungkidul district of Yogyakarta, Java Island, Indonesia. Porok beach is dominated by a rocky substrate, which would be the ideal substrate for macroalgae. The development of coastal areas as a tourism destination is feared to have an impact on macroalgae biodiversity. Comprehensive efforts are required to protect the coastlines of Porok Beach as sources of macroalgae germplasm that will ensure the survival of coastal biodiversity in Gunungkidul. So, it is necessary to study macroalgae diversity in Porok Beach to obtain a preliminary data to conserve. the macroalgae in the area. This study aims to monitor the presence of the macroalgae on Porok Beach. Purposive random sampling was used in the study, which took place on October 17th, 2020. Water temperature and pH are the ecological parameters that are measured. Seaweed specimens were collected only from those that were attached to the substrate (no floating specimens were collected) during low tide and then placed in ziplock plastic bags. Macroalgae species were identified to determine macroalgae species based on taxonomic keys using FAO species identification Guide for Fishery From the results of the study, Porok Beach was home to 17 species of macroalgae, eight of which were classified as Chlorophyta, 3 species are classified as Phaeophyta, and 6 species are classified as Rhodophyta.